Determination of Appropriate Artery Cannula Diameter by Measuring Radial Artery Diameters Using Ultrasonography and Investigation of the Correlation of “Allen Test” with Doppler Ultrasonography - Akkuş, Ayşe Sıla; Nizamoğlu, Aylin; Akyol Beyoğlu, Çiğdem; Ekici, Birsel; Erbabacan, Şafak Emre; Köksal, Güniz M.; Altındaş, Fatiş (Cerrahpaşa Medical Journal, 2023)
Objective: We aimed to investigate the correlation of radial artery diameters with age, sex, height, and weight to determine a suitable size for can- nulation and to assess the adequacy of the Allen test evaluating ulnar flow via ultrasonography. Methods: A total of 500 patients with American Society of Anesthesiologists physical status I and II aged between 18 and 60 years without vascular pathology were enrolled. Allen test was performed at the nondominant hand, and radial artery diameter and ulnar artery flow were measured by ultrasonography before sedation. Measurements were repeated 5 minutes after anesthesia induction. Pearson’s chi-square and Fisher's exact tests were used to compare categorical variables. Student’s t-test and one-way analysis of variance test were used to compare continuous variables. Pearson cor- relation coefficient analysis was used to compare measurements. The statistical significance was accepted at a P value less than .05. Results: The mean diameter of the radial artery was found smaller before (2.35 ± 0.39 mm) than after (2.57 ± 0.42 mm) anesthesia. The mean diam- eter of the radial artery was smaller in patients < 30 years of age than in the other groups before and after anesthesia. The mean diameter of the radial artery before anesthesia was smaller in normal and underweight patients than in the other groups and was smaller after anesthesia in underweight patients than in the other groups. The mean diameter of the radial artery in smokers before and after anesthesia was narrower in non-smokers. We did not find a relationship between ulnar blood flow and the Allen test. Conclusion: Gender, height, weight, and age should be considered for proper radial arterial cannulation. Allen test may not be enough to show the ulnar flow. Cite this article as: Akkuş AS, Nizamoğlu A, Akyol Beyoğlu Ç, et al. Determination of appropriate artery cannula diameter by mea- suring radial artery diameters using ultrasonography and investigation of the correlation of “Allen Test” with doppler ultrasonography. Cerrahpaşa Med J. 2023;47(2):176-181.